2016
DOI: 10.5812/ircmj.27932
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Diclofenac Versus Rectal Paracetamol: Comparison of Antipyretic Effectiveness in Children

Abstract: BackgroundFever is the most common complaint in pediatric medicine and its treatment is recommended in some situations. Paracetamol is the most common antipyretic drug, which has serious side effects such as toxicity along with its positive effects. Diclofenac is one of the strongest non-steroidal anti-inflammatory (NSAID) drugs, which has received little attention as an antipyretic drug.ObjectivesThis study was designed to compare the antipyretic effectiveness of the rectal form of Paracetamol and Diclofenac.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…An overview on the efficacy and safety of oral and rectal diclofenac is given in Table 6 [ 42 , 244 , 288 – 290 ]. It was consistently shown that children and infants will not benefit from doses higher than 1 mg/kg [ 38 , 43 ].…”
Section: Discussion Of the Specific Nsaids And Overall Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview on the efficacy and safety of oral and rectal diclofenac is given in Table 6 [ 42 , 244 , 288 – 290 ]. It was consistently shown that children and infants will not benefit from doses higher than 1 mg/kg [ 38 , 43 ].…”
Section: Discussion Of the Specific Nsaids And Overall Conclusionmentioning
confidence: 99%
“…showed that effective antipyresis was achieved with 2 mg/kg diclofenac administered intramuscularly, and that infants < 24 months of age had a more rapid onset of antipyresis compared with children <60 months of age [ 289 ]. Rectal diclofenac provided more effective antipyresis compared with rectal acetaminophen in children aged 1–6 years [ 290 ] and can be used for children suffering from vomiting or patients being on nihil per os’ status [ 292 ]. In the postoperative setting, rectal diclofenac allowed earlier solid intake in children aged 3–14 years after tonsillectomy, suggesting an anti-inflammatory effect compared with acetaminophen [ 288 ].…”
Section: Discussion Of the Specific Nsaids And Overall Conclusionmentioning
confidence: 99%
See 1 more Smart Citation